Regulatory Barriers in Collecting Assessment Rates Arrears of Local Authorities in Malaysia - Mohd, Elina; Ayub, Zainal Amin; Mohd Anuar, Haslinda (Khalsa Publications, 2018)
Assessment rate is the only local tax form in Malaysia and it is a main source of income for local authorities. It is also may be considered as a potential source of income to replace grants from the Federal Government. Revenue from assessment rates is crucial for the local authorities to pay for services and maintenance in the local authority administrative areas, as well as for their effective administration and service delivery system. However, arrears of assessment rates of local authorities in Malaysia have become national issues and it becomes more challenging over time to recover the arrears. Local authorities are faced with various issues and problems in collecting and enforcing arrears of assessment rates. Thus, it is the aims of this study to examine the problems of rate assessment arrears collection and to identify regulatory barriers in collecting assessment rates arrears amongst local authorities. The scope of the study however is limited to the local authorities in the northern region of Malaysia only. The study employs socio-legal research where apart from library based research, questionnaires were distributed to legal officers, valuation officers and accountants from various department of local authorities. This study finds that the amount of revenue collected is decreasing due to loopholes of the law and ineffective enforcement of the law by local authorities. It is also found that the local authorities? officers lack of understanding of the law and procedures on the collection of assessment rates arrears. It is suggested that the law should be amended and the training should be provided for the improvement of the assessment rate collection